Determination of the Incidence of Dental Caries and Periodontal Disease among Shiraz, Iran, Residents: - Karimi, Noozhan; Khadem, Parvin; Esfahanian, Vahid (Galen Medical Journal, 2013)
Introduction: Dental caries and periodontal disease are among the most common infectious diseases in the world. DMFT (Decayed, Missing, Filled, Teeth), CPITN (Community Periodontal Index of Treatment Needs), and plaque indices are applied as suitable criteria for evaluating these two diseases and oral health. Given the significance of dental caries and periodontal disease, the objective of this study was to determine the incidence of dental caries and periodontal disease in the Iranian city of Shiraz. Material and Methods: The samples were evaluated in the four categories of medical, manufacturing, educational, and office centers within Shiraz, and then the DMFT, CPITN, and plaque indices in addition to nutrition status were all measured among them. Results: Having considered the DMFT to be below 15% and the CPITN less than 1.5 (the variables’ mean in the population under study), respectively, as resistant to dental caries and periodontal disease while at the same time taking into account the plaque index of less than 1.25 (mean) as the low level of this very index not disregarding the nutritional status of the population under study: the resistant individuals ratio to the two diseases equaling 10%, those individuals prone to these two diseases equaling 55%, the ratio of resistant people to periodontal disease and, simultaneously, prone to dental caries equaling 14%; and, lastly, the ratio of individuals resistant against dental caries simultaneously prone to periodontal disease equaling 20% (estimated). Conclusion: The research was performed in medical, manufacturing, educational, and office centers in Shiraz, Iran. There was no significant difference in terms of periodontal disease and dental caries between the four groups. [GMJ. 2012;1(2):66-71]